DİL BİLİMSEL ALAN OLARAK FIKHU’L-LUGA, DOĞUŞU, KONUSU VE ÖNEMİ - DAĞ, AHMET (Scientific Journal of Faculty of Theology, 2015)
Our main goal in this study introduces the "Fıqh-ulLuga", which is the scientific field of language. For this reason, the area in question and place a true field means to provide the first the "Fıqh-ulLuga" that emerged up to the fourth Hijri century, we will discuss briefly their language studies. Thus, it will be easie r to identify the causes of the emergence of this field. Supsequently, we will be promoting the "Fıqh-ulLuga" in the literature of both classical period and the modern period by the emergence of the field. Finally, we will examine the importance and the subject of the "Fıqh-ulLuga". In our paper we analyze the main problems are as follows: What exactly does the "Fıqh-ulLuga" mean? Can the "Fıqh-ulLuga" be regarded as an independent field such as grammar, syntax and vocabulary in Arabic linguistic? Which has the ―Fıqh-ulLuga‖ has emerged? What are the main issues that are looking at this area? What is the importance of the Arabic language in science?